Studying on Antifungal Activities of Streptomyces Isolated from Soil and Its Biocontrol Potential Against Fusarium of Chili’s Root Rot Disease - Nguyễn Anh, Dũng (International Journal of Applied Biology, 2024)
Seven Streptomyces strains from chili farm soil, including Strep-1, Strep-2, Strep-4, Strep-5, Strep-6, Strep-8, and Strep-10, were screened for their antifungal activities against Fusarium sp. of chili's root rot disease. The results showed that Streptomyces sp. Strep-4 and Streptomyces sp. Strep-8 performed potential abilities to control the pathogenic Fusarium of which means of antifungal efficacies were 43,88 ± 3,21% and 51,8 ± 2,54%, in turn. Extensive researches on the effects of inoculum factors on antifungal activity of Streptomyces sp. Strep-8 resulted that this strain spontaneously synthesized the antifungal compounds to control Fusarium in the culture condition with pH 7, 40oC of culture temperature, and 7 days of culture time. The results proved that Streptomyces sp. Strep-8 with its thermophilic ability not only provided significant inhibitory activity against pathogenic Fusarium sp. in vitro also promised to be a potential biological control agent to eliminate this fungus on fields. Moreover, using Streptomyces sp. Strep-8 as a biological control agent helps reduce the use of fungicides which contributes to boosting the sustainability of agricultural ecosystems worldwide.